1984
DOI: 10.2135/cropsci1984.0011183x002400050021x
|View full text |Cite
|
Sign up to set email alerts
|

Taproot‐Elongation Rates of Soybean Cultivars in the Glasshouse and Their Relation to Field Rooting Depth1

Abstract: Deeper rooting should improve soybean [Glycine max (L.) Merr.] water stress avoidance by increasing water uptake from deep soil strata. Because taproots are initially the deepest segment of soybean root systems, soybean genotypes with rapidly elongating taproots may have deeper root systems than genotypes with slowly elongating taproots. Taproot‐elongation rates of 105 soybean cultivars from Maturity Groups I, II, and III were measured in a glasshouse using clear plastic tubes filled with vermiculite and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 0 publications
3
42
0
1
Order By: Relevance
“…A more intense soil exploration can be expected under conditions of water deficiency (Maertens, 1986), but no agreement exists on the soil depth explored by soybean roots. Mayaki et al (1976), Kaspar et al, (1978Kaspar et al, ( , 1984; Willat and Taylor (1978) ;Reicosky and Deaton (1979); Hoogenboom et al (1987), found soybean roots at 1-2 m, and Maertens (1986) at 2-3 meters; but Cox and Jolliff (1987) reported little soil water absortion below 90 cm.…”
Section: Introductionmentioning
confidence: 99%
“…A more intense soil exploration can be expected under conditions of water deficiency (Maertens, 1986), but no agreement exists on the soil depth explored by soybean roots. Mayaki et al (1976), Kaspar et al, (1978Kaspar et al, ( , 1984; Willat and Taylor (1978) ;Reicosky and Deaton (1979); Hoogenboom et al (1987), found soybean roots at 1-2 m, and Maertens (1986) at 2-3 meters; but Cox and Jolliff (1987) reported little soil water absortion below 90 cm.…”
Section: Introductionmentioning
confidence: 99%
“…Soybean cultivars differ in their rate of downward growth during specific shoot development stages and in their maximum rooting depth on specific. Cultivars selected for rapid taproot elongation rates in a greenhouse trial were found to have greater rooting depths in rhizotron and field trials than cultivars selected for slow taproot elongation (Kaspar et al, 1984).…”
Section: Rooting Depth and Root Distributionmentioning
confidence: 94%
“…In a review of depth development of roots with time for 55 crop species (Borg and Grimes, 1986), it was shown that maximum rooting depth for most crop species was generally achieved at physiological maturity. Kaspar et al, (1984) noted that the rate of soybean (Glycine max L. Merr.)…”
Section: Root Growth As a Function Of Plant Agementioning
confidence: 99%
“…Merr.) are diffuse-rooted, but the taproot elongation rate initially determines rooting depth and some cultivars have a more dominant taproot than others (Kaspar et al, 1984). White clover cultivars also show a range of relative dominance of taproots (Caradus, 1981) as do alfalfa cultivars (McIntosh and Miller, 1980).…”
Section: Dicotyledonous Root Systemmentioning
confidence: 99%